Adaptasi Kebiasaan Baru Masyarakat Saat Pandemi Covid-19 (Studi Kasus Adaptasi Institusi Pendidikan di Nagari Tigo Koto Silungkang Kecamatan Palembayan Kabupaten Agam) - Vioni Pebriancha; Nilda Elfemi; Ikhsan Muharma Putra (Horizon, 2021)
This research is motivated by the existence of a virus called Covid-19. Covid-19 is a virus that can cause death in humans and animals. This virus is known to cause respiratory infections ranging from mild flu to more severe illnesses in humans. The implementation of the adaptation of new habits has been implemented by the Indonesian government since July 2020. With the importance of new habits in educational institutions, to what extent are the adaptations of new habits implemented by educational institutions. The formulation of the research problem is how to apply the adaptation of the community's new habits during the Covid-19 pandemic in Nagari Tigo Koto Silungkang, Palembayan District, Agam Regency. The theory used in this study is the structural functional theory proposed by Talcott Parsons. The research approach used is a qualitative approach with a descriptive analytical research type. The types of data used in this study are primary data and secondary data. There were 7 informants involved in this study. Data collection methods were used in two ways, namely observation, in-depth interviews and document studies. To achieve the validity of research data using triangulation techniques. Meanwhile, the unit of data analysis used was a group with data analysis by Miles and Huberman, namely data reduction, data presentation, data presentation and conclusion drawing. From the results of the study, it can be concluded that the educational institutions in Nagari Koto Silungkang, Palembayan District, Agam Regency consist of SMP Negeri 2 Palembayan, MTs Swasta Tantaman and MTs Swasta Gumarang that each institution has prepared important facilities for adapting new habits. Adaptation of new habits has been carried out in accordance with health protocols, violations that occur in each institution are the difficulty of students wearing masks after being outside the classroom for reasons of shortness of breath, then each institution also builds and forms a school organization system in implementing adaptation of new habits by form a school task force team. Keywords: Adapt New Habbits, Covid-19 Pandemic